2020
DOI: 10.20944/preprints202009.0391.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alpha-glucosidase and Alpha-amylase Inhibitory Activities, Molecular Docking and Antioxidant Capacities of Salvia Aurita Constituents

Abstract: Diabetes mellitus (DM) is one of the most dangerous metabolic diseases with high rate of mortality worldwide. It is well known that insulin resistance and deficiency in insulin production from pancreatic β-cells are the main characteristic of DM. Due to the detrimental side effects of the current treatment, there is a considerable need to develop new effective antidiabetic drugs, especially alpha-glucosidase and alpha-amylase inhibitors with lesser adverse effects. These inhibitors are known to be dir… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…These bright yellow crystals were vacuum ltered, washed thrice with ice-cold ethanol, recrystallized from ethanol, and dried in the desiccator. Color: yellow; yield: 80%; melting point: 85 °C; UV/Vis: 271, 326, 420; ESI-MS: 296.20[M + H] + ; FT-IR: (KBr disc) n/cm −1 : 1618 (HC]N), 1547 (C]C), 1228 (C-N), 2908, 2848 (C-H-aromatic, str), 3317 (OHaromatic), 3062 (vinyl CH 2 , str); 1 H-NMR (400 MHz, DMSO-d 6 ) d ppm; 1.70 (m, CH 2 , 1-adamantane), 1.87 (d, CH 2 , 1-adamantane), 2.08 (m, CH 2 , 1-adamantane), 4.99 (d, CH 2 , methylene), 5.02 (t, H, 1-ethylene), 5.07 (t, H, 1-ethylene), 5.93 (m, H, 1ethylene), 14.83 (s, OH-alcohol), 6.79 (t, CH-benzylidenimin), 7.12 (d, CH-benzylidenimin), 7.33 (d, CH-benzylidenimin), 8.55 (s, CH]N) 13…”
Section: Synthesis Of (E)-2-((adamantan-1-ylimino)methyl)-6allylpheno...mentioning
confidence: 99%
See 1 more Smart Citation
“…These bright yellow crystals were vacuum ltered, washed thrice with ice-cold ethanol, recrystallized from ethanol, and dried in the desiccator. Color: yellow; yield: 80%; melting point: 85 °C; UV/Vis: 271, 326, 420; ESI-MS: 296.20[M + H] + ; FT-IR: (KBr disc) n/cm −1 : 1618 (HC]N), 1547 (C]C), 1228 (C-N), 2908, 2848 (C-H-aromatic, str), 3317 (OHaromatic), 3062 (vinyl CH 2 , str); 1 H-NMR (400 MHz, DMSO-d 6 ) d ppm; 1.70 (m, CH 2 , 1-adamantane), 1.87 (d, CH 2 , 1-adamantane), 2.08 (m, CH 2 , 1-adamantane), 4.99 (d, CH 2 , methylene), 5.02 (t, H, 1-ethylene), 5.07 (t, H, 1-ethylene), 5.93 (m, H, 1ethylene), 14.83 (s, OH-alcohol), 6.79 (t, CH-benzylidenimin), 7.12 (d, CH-benzylidenimin), 7.33 (d, CH-benzylidenimin), 8.55 (s, CH]N) 13…”
Section: Synthesis Of (E)-2-((adamantan-1-ylimino)methyl)-6allylpheno...mentioning
confidence: 99%
“…α-Amylase is involved in the digestion of carbohydrates, while α-glucosidase is involved in the digestion of starch and disaccharides into glucose. 13 These enzymes can be suppressed by effective inhibitors to treat diabetes. 14 A large number of coordinated compounds such as chromium, cobalt, zinc, vanadium, tungsten, and molybdenum have been used in the remediation of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction analysis of the SPPs and reference acarbose showed that they have a close binding pattern as the native myricetin and interacted with the catalytic residues through hydrogen bonds and hydrophobic interactions. The acarbose structure conducted both hydrogen bonds and hydrophobic interactions with the active site residues of the target enzyme as reported in previous studies (Singla et al, 2016;Etsassala et al, 2020;Ogunyemi et al, 2020). The hydroxyl groups on C-20 and C-14 of the pregnane structure of the P1 donated hydrogen to the side chains of Glu233 and Asp300 of HPA, respectively, with bond distances less than 2.9 Å to form conventional hydrogen bonds.…”
Section: Discussionmentioning
confidence: 86%
“…This prevents the postprandial glucose level from increasing, which plays a significant role in the development of cardiovascular diseases (Joshi et al 2015;Jiang et al 2017). Thus, there is an urgent need to discover AGI from plants since they are known sources of bioactive compounds (Etsassala et al 2020) and they are more accessible to people, especially to those who are in remote areas who use plants as their primary treatment (Singab et al 2014).…”
Section: Introductionmentioning
confidence: 99%